Anxiety and depression symptoms after virological clearance of COVID‐19: A cross‐sectional study in Milan, Italy - Tomasoni, Daniele; Bai, Francesca; Castoldi, Roberto; Barbanotti, Diletta; Falcinella, Camilla; Mulè, Giovanni; Mondatore, Debora; Tavelli, Alessandro; Vegni, Elena; Marchetti, Giulia; d'Arminio Monforte, Antonella (Journal of medical virology, 2021)
Prevalence of anxiety or depression was investigated in 105 coronavirus disease 2019 (COVID‐19) patients at 1 to 3 months from virological clearance by hospital anxiety and depression scale (HADS‐A/D). 30% of patients displayed pathological HADS‐A/D, 52.4% showed persistent symptoms. Pathological patients with HADS‐A/D more commonly reported symptom persistence, even after adjustment for age, gender, and disease severity. Psychological assessments should be encouraged in COVID‐19 patients' follow‐up. Highlights 1‐3 months after clinical and virological recovery from symptomatic COVID‐19 disease, 30% and 52.4% of patients still presented psychological and physical symptoms, respectively Persistence of anxiety and depression was independently associated with ongoing physical symptoms Psychological evaluations should be included in the follow‐up of COVID‐19 patients.